Children's representations of nature using photovoice and community mapping: perspectives from South Africa. Issue 1 (1st January 2017) - Adams, Sabirah; Savahl, Shazly; Fattore, Tobia
ABSTRACT: The aim of the study was to explore children's representations and perceptions of natural spaces using photovoice and community mapping. The sample consisted of 28 children aged 12–14 years residing in urban and rural communities in the Western Cape, South Africa. Data were collected by means of a series of six focus groups interviews (three photovoice discussion groups and three community mapping discussion groups). For the photovoice missions, children were provided with a 28-exposure disposable camera and given 1 week to complete their missions. Thematic analysis was employed to analyse the data. Three key themes emerged, namely: safe spaces in nature, unsafe spaces in nature, and children's favourite places in nature. Socio-economic status (SES) was found to be a determining factor in how children make sense of natural spaces. Children from low SES communities indicated being more constricted in their mobility, and were unable to access to safe natural spaces compared to the children from the middle SES community. It is recommended that an expedient starting point would be to work towards and build environmentally and child-friendly communities for children, with children as key contributors in the planning process using a child participation framework.